Unexpected Nitrogen Sources in a Tropical Urban Estuary. Issue 3 (21st March 2020) - Oczkowski, Autumn J.; Santos, Emily A.; Martin, Rose M.; Gray, Andrew B.; Hanson, Alana R.; Watson, Elizabeth B.; Huertas, Evelyn; Wigand, Cathleen
Abstract: Tropical urban estuaries are severely understudied. Little is known about the basic biogeochemical cycles and dominant ecosystem processes in these waterbodies, which are often low lying and heavily modified. The San Juan Bay Estuary (SJBE) in San Juan, Puerto Rico, is an example of such a system. Over the past 80 years, a portion of the estuary has filled in, changing the hydrodynamics and negatively affecting water quality. Here we sought to document these changes using ecological and biogeochemical measurements of surface sediments and bivalves. Measurements of sediment physical characteristics, organic matter content, and stable isotope ratios (δ 13 C, δ 15 N, δ 34 S) illustrated the effects of the closure of the Caño Martín Peña (CMP) on the hydrology and water quality of the enclosed and semi‐enclosed parts of the estuary. The nitrogen stable isotope (δ 15 N) values were lowest in the CMP, the stretch of the SJBE that is characterized by waters with low dissolved oxygen and high fecal coliform concentrations. Despite this, the results of this study indicate that nitrogen (N) contributions from N‐fixing, sulfate‐reducing microbes may meet or even exceed contributions from urban runoff and sewage. While the importance of sulfate reducers in contributing N to mangrove ecosystems is well documented, this is the first indication that such processes could be dominant in an intensely urban system. It also underscores just how little we know about tropical coastal ecosystems in densely populated areas throughout the globe. Key Points: We lack a basic understanding of the biogeochemical dynamics of tropical, urban coastal regions Sediment geochemistry from San Juan Bay Estuary's most urbanized region suggests that nitrogen fixation is an important nitrogen source Nitrogen fixation by sulfate‐reducing microbes is well documented in mangroves, but never in such an intensely urban system